The perceptions of first year students on the impact of relocation on their adjustment at university : a relocation study. - Nkuna, Joy Manini (My University, 2009)
The research aims to establish the perceived impact of relocation on first year student’s ability to cope with academic demands at University. The research intends to answer the following questions: How do first year students perceive their adjustment at University? Has the relocation impacted on the students functioning on any level? For example: -Academically, Emotionally, Physically and Socially. A large number of young adults relocate due to the need to pursue their chosen careers at the University. However, this happens at a time in their life when there is a lot of turmoil around social and individual identity and the pressures from society to achieve, including pressures to secure their future. This happens independently from parents and relevant social ties when students study away from home. A qualitative methodology was used for the research. The sample consisted of 10 Black female post matric first year students at University. The age range of participants was between 17 and 20. Data was collected through the use of semi structured interviews. Gathered data was analyzed using thematic content analysis. This involves organizing the data into categories on the bases of the themes and concepts. The concepts were then linked up in the form of a sequence. Eight steps were then followed when analyzing the data, which forms part of the criteria for thematic content analysis. Results obtained indicate that students find relocation to be a perturbing experience which pushes one out of their comfort zone into the unknown. This experience forces one to make numerous adjustments. The move taps into one's ability to deal with ambiguities, function independently and implement a task to deal with unanticipated challenges. Thus students are expected to take on the role of young adulthood. This brings with it the reality that they now have to be independent. As a result of this, most students get involved in what is called goal modification, namely focusing on what they would like instead of focusing on what their parents would want. The process is challenging as one is going through a process of loss and, in other ways, gain. The loss of social capital is felt as having a negative impact on academic performance. This is because students loose their source of motivation, support and reliable company. They now have to source it within themselves, an attribute which has proven to be difficult. Relocation is viewed as a compounding variable to other challenging factors to students. Hence the students’ relocation is perceived to be a variable which tends to have a negative affect on students’ academic performance. This is due to the fact that relocation tends to create a sense of discontinuity from known academic structures, social support ties and familiar surroundings. The loss of the above mentioned factors tends to aggravate the process of academic adjustment.
Keywords: Relocation; Coping; Adjustment; First year university students; Impact